DINAMIKA INTERAKSI AGEN DAN STRUKTUR DALAM MENCEGAH KONSENTRASI KEPEMILIKAN MEDIA TELEVISI - Nursatyo, Nusatyo (Universitas Muhammadiyah Surakarta, 2016)
The acquisition PT IDKM by PT EMTEK that have an impact of the unification INDOSIAR?and SCTV in the same holding company between period 2011 ? 2012, bring a nation-wide?discussion about concentration of media television ownership in Indonesia. Broadcast act?no.32/2002 with Indonesia Broadcasting Commision as an independent regulatory body?considered weak in the face of concentration. This paper provide a comprehensive description?about the dynamics interaction between agent and structure of Indonesian broadcasting?system particularly in order to organize commercial television media ownership.